ANALISIS SASARAN KESELAMATAN PASIEN DILIHAT DARI ASPEK PELAKSANAAN IDENTIFIKASI PASIEN DAN KEAMANAN OBAT DI RS KEPRESIDENAN RSPAD GATOT SOEBROTO JAKARTA - Syifa Sakinah; Putri Asmita Wigati; Septo Pawelas Arso (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Hospitals are obligated to provide services according to the patient's rightsand patient’s safety. The accuracy of patient identification and drug preservation (high alert) are parts of patient safety. At Presidential Hospital RSPAD Gatot Soebroto there are still patients who are not well identified and there are drugs (high alerts) that are not placed according to the SOP. This study aimed to found out the implementation of patient identification and drug safety (high alert) in the inpatient care unit of Presidential Hospital RSPAD GatotSoebroto by using theory of system. This research method was a qualitative descriptive by using instruments of research such as interview guide and observation sheets. Interviews were conducted with the head of the room, the secretary of the quality committee, caretaker nurse and patient safety staff of Presidential Hospital RSPAD GatotSoebroto. The results showed that the implementation of patient identification and drug safety (high alert) has been run out but not yet fully complied with as stipulated in PMK 1691/MENKES/PER/VII/2011. This was happenedbecause the human resources were inadequate, the lack of training on the nurses of the implementers, the nurses were less in compliance with the established SOP, lack of the commitment of nurses who implement the task, the delay in submitting patient safety report to KMKP. Suggestions from this research are activating the person in charge of TKPRS in the inpatient unit, assembling regular training, follow-up of SOP compliance related to monitoring patient identification and drug safetyby holding cctv and patient questionnaires for nursing evaluation, and improving the task of recording and reporting culture of patient's case.